The Stress of a Cooperative Breeder - Mileva, Viktoria R. (My University, 2009)
In this thesis I examined behavioural, physiological, and molecular aspects of the stress response of the highly social cichlid Neolamprologus pulcher. Through this work, I established that dominant individuals within a group have higher baseline stress levels (as measured by plasma circulating cortisol concentrations) than subordinate group members, and hypothesize that this is due to the high demands placed on dominant individuals in both acquiring and maintaining their dominance status. Additionally, social behaviours, and activity levels were positively correlated with stress levels in subordinate males but these correlations were not observed in any other social class. Life history traits of males may explain this pattern, as subordinate males are arguably the social class with least stability in a group, and may need to appease dominant individuals in order to be allowed to stay; this may in tum cause stress. I was also able to establish that while dominant individuals had higher resting cortisol levels than subordinates, they were in no way maximal, as the application of a 10 minute stressor caused large increases above resting levels (>10 fold in magnitude) in circulating cortisol levels of both social classes and in both sexes. As an extension to the characterization of the stress response in N. pulcher, we examined differences in corticosteroid receptor levels between dominants and subordinates. This will paint a much fuller picture of the stress response in N. pulcher and highlight differences and similarities between stress responses in each social class, both physiologically and at the molecular level.
In a second experiment, dominant female breeders were repeatedly stressed to assess possible maternal and offspring fitness costs. Through this manipulation we found that stressing females resulted in a longer interval between spawning events, and decreased maternal growth rates. Additionally there was a significant decrease in the number of eggs laid, as well as egg size in stressed mothers compared to those left unstressed. Helpers within a group seemed to have no effect on the above-mentioned characteristics, however mothers without helpers released highly variable cortisol concentrations during the first and second lay, while those with helpers saw less variability in the concentration of cortisol they released into eggs.
The results presented in this thesis shed light on the stress responses of N. pulcher, highlighting the impacts that within-group social dynamics have on stress levels, and their potential impacts on maternal and (possibly) offspring fitness.
Keywords: Social and Behavioral Sciences; Social and Behavioral Sciences